Predictors of well-being and growth following exposure to interpersonal violence among emerging adults - Weierbach, Gabrielle (2017)
Interpersonal violence is considered a serious health problem given the potential for contributing to negative outcomes among victims. In recent decades, however, findings from studies have suggested that although the experience of interpersonal violence is associated with a greater risk for compromised psychosocial adjustment, a majority of survivors demonstrate a more resilient profile or even growth following trauma. The present study examined select components of one of those models, the recent Resilience Portfolio Model, to aid in the understanding of important qualities that can be harnessed for the promotion of well-being and growth among survivors. This study examined if character strengths, which have not been studied previously in relation to IPV, predict well-being following exposure to violence. Moreover, it explored whether or not secure attachment and perceived social support may increase the experience and expression of positive emotions and character strengths. In addition, we examined how the capacity to generate and sustain positive emotions relates to emotion regulation, specifically in the context of victimization among emerging adults in college. Results of the study support the notion that - in lieu of trauma or IPV - it is possible to have positive experiences. Our findings suggest an association between emotion regulation strategies and the experience of positive emotions. Furthermore, few of the character strengths were related to IPV variables in this sample, and those that were indicated an opposite relationship than expected. Finally, the study supports the importance of secure attachment for one’s perception of social support. Currently, many violence prevention programs tend to focus on determining risk factors and warning signs rather than building a foundation of skills for healthy relationships, self-efficacy and others. These findings present those assets and resources within an individual that work to enhance well-being. Focusing on these skills and building strengths could facilitate alleviation of negative symptoms. Limitations and suggestions for future research are also discussed.